Analysis and interpretation of botanical remains from Sibudu Cave, Kwazulu Natal - Scott, Christine (My University, 2006)
The identification and analysis of seeds (including fruits and nuts) from second millennium AD deposits at Sibudu Cave, KwaZulu-Natal, constitute the first in-depth archaeobotanical study of seeds in South Africa. The study highlights problems in the reconstruction of past vegetation and climatic variables from seed data. The Sibudu seed assemblage produced no evidence to suggest vegetation change in the Sibudu area during the last 1000 years. Either it is not possible to identify short-term fluctuations in indigenous vegetation from seed data, or the evidence of vegetation change has been masked by the influence of the perennial Tongati River, depositional history, differential preservation and recovery, and identification difficulties. Actualistic studies of seeds on the cave floor, the first of such studies in South Africa, indicated a range of non-human agents of seed accumulation and post-depositional redistribution. Definitive statements about people/plant relationships are problematic because of the number of agents of seed accumulation.
Master of Science - Archaeology
Keywords: botanical; cave; sibudu; kwazulu; natal